Influence of spacing of waterwall tubes on their operating parameters - Majdak, Marek (Archives of Thermodynamics, 2026)
The article presents the results of thermal and flow analysis of the working conditions of neighbouring waterwall tubes, loaded with heat streams of different values for two different widths of tube spacing. The numerical model used for the analysis allows us to calculate the temperature distribution in the tubes and in the fluid flowing through them at each time step, depending on the thermophysical parameters of the fluid and the material from which the tubes and fins were made. By using the algorithm, it is possible to precisely determine the three-dimensional temperature distribution in the tubes, allowing us to identify the locations where the greatest temperature differences occur and where the highest thermal stresses may develop. The analysis of several adjacent tubes makes it possible to determine the effect of temperature differences in the tubes and the fins connecting them, and to collect data that may be used to determine the stress distribution in the tubes and fins. In the presented Case 3, smooth tubes connected by fins were used, and the heat flux on the centre tube was 50% higher than that on the outer tubes.